Mutation update for the ACTN2 gene. Issue 12 (27th September 2022) - Ranta‐aho, Johanna; Olive, Montse; Vandroux, Marie; Roticiani, Giorgia; Dominguez, Cristina; Johari, Mridul; Torella, Annalaura; Böhm, Johann; Turon, Janina; Nigro, Vincenzo; Hackman, Peter; Laporte, Jocelyn; et al.
Abstract: ACTN2 encodes alpha‐actinin‐2, a protein expressed in human cardiac and skeletal muscle. The protein, located in the sarcomere Z‐disk, functions as a link between the anti‐parallel actin filaments. This important structural protein also binds N‐terminal titins, and thus contributes to sarcomere stability. Previously, ACTN2 mutations have been solely associated with cardiomyopathy, without skeletal muscle disease. Recently, however, ACTN2 mutations have been associated with novel congenital and distal myopathy. Previously reported variants are in varying locations across the gene, but the potential clustering effect of pathogenic locations is not clearly understood. Further, the genotype‐phenotype correlations of these variants remain unclear. Here we review the previously reported ACTN2 ‐related molecular and clinical findings and present an additional variant, c.1840‐2A>T, that further expands the mutation and phenotypic spectrum. Our results show a growing body of clinical, genetic, and functional evidence, which underlines the central role of ACTN2 in the muscle tissue and myopathy. However, limited segregation and functional data are available to support the pathogenicity of most previously reported missense variants and clear‐cut genotype‐phenotype correlations are currently only demonstrated for some ACTN2 ‐related myopathies.